Between Germany and Indonesia: The Difference of Green City Discourse in Freiburg and Surabaya - Nugroho, Rio Satria; Nirmala, Lintang Wahyusih (Jogjakarta Communication Conference (JCC), 2024)
Green City as a form of environmental sustainability has been implemented in several cities including Freiburg, Germany and Surabaya, Indonesia. This paper discusses the comparison of green city discourse applied in the two cities. Even though it is not an equal comparison, acknowledging the difference in context and cultural nuances between Surabaya and Freiburg is crucial for understanding the significance comparison. It offers valuable insights into the diverse ways in which environmental communication is practiced and perceived across different cultural settings. This paper aims to see the differences in the promotion of green city discourse in the two cities that have been awarded as Green City in each country. It reflects on how these two cities are implementing the practice of green city values. On a larger scale, it can be used to review environmental issues and responses in the two cities. This research used comparative case studies to see the discourse in Freiburg and supported by observation for the application in Surabaya. The discourse framework was obtained from John Dryzek, environmental discourse. The delivery of green city discourse in Freiburg is seen as more massive and continuous by implementing environmental values in city regulations and policies, while the promotion of green city discourse in Surabaya has not gone that far. The echo of communication between community groups about the environmental crisis is routinely held in Freiburg through several actions or programs that have not been found in Surabaya. It is expected that this paper can be a spark for further research in looking at communication practices and the realization of green cities, especially in Indonesia.